Effect of moderate and high intensity chronic exercise on the pancreatic islet morphometry in healthy rats: BDNF receptor participation. Issue 1 (2nd January 2017) - Jiménez-Maldonado, Alberto; Virgen-Ortiz, Adolfo; Melnikov, Valery; Rodríguez-Hernández, Alejandrina; Gamboa-Domínguez, Armando; Montero, Sergio; Muñiz-Murguía, Jesús; Lemus, Mónica; Roces de Álvarez-Buylla, Elena
ABSTRACT: The function and morphology of β-cells is largely dependent on insulin demand. As β-cells cover a bigger cell proportion in pancreas islets, changes of insulin producer cells affect the whole pancreatic islet morphology. Growth factors as the neurotrophins regulate the pancreas physiology, besides; physical exercise increases insulin sensitivity, and further modifies brain derived neurotrophic factor (BDNF) concentration in plasma. The aim of this study was to investigate the effects of chronic exercise (running in a treadmill for 8 weeks) intensity on pancreatic islet morphometry in healthy state. The BDNF receptor effect on the pancreatic islet morphometry was also evaluated. Adult male Wistar rats were divided in 6 groups: Control (C); moderate intensity training (MIT); high intensity training (HIT) did not treat with BDNF receptor inhibitor (K252a), and C, MIT and HIT treated with K252a. The results shown that chronic exercise induces β-cells hypertrophy without BDNF receptor participation. On the other hand, the moderate exercise increases the number of β cells per islet; the last effect does not require TrkB participation. In sedentary conditions, the K252a treatment reduced the β-cell density. Exercise intensity has differential effects on pancreas islet morphometry in healthy model; furthermore, BDNF receptor plays a role to maintain the amount of β-cells in sedentary state.